Diagnosis of bacterial vaginosis: comparison of Nugent’s and novel microscopic method - Nenadić, Dane; Ribis, Snežana; Pavlović, Miloš; Baskić, Dejan (Vojnosanitetski pregled, 2022)
Background/Aim. Bacterial vaginosis (BV) is a common cause of vaginal discomfort in women. The aim of this study was to compare Nugent’s scoring system and novel microscopy method, introduced in our laboratory and used in BV diagnosis. Methods. This study included 705 pregnant and asymptomatic women between 24 and 28 weeks of pregnancy. The degree of agreement between methods was determined by the kappa (κ) index. The sensitivity, specificity, positive and negative predictive value of the novel microscopy method was compared to Nugent’s score as standard. Results. Based on the scoring system of both methods, Nugent’s and novel microscopy method, BV was diagnosed in 21% and 25% of women, respectively. Despite the disparities among diagnostic criteria, which mainly concerned classification of intermediary samples, the degree of agreement between categories, determined by κ index, was satisfactory: Nugent’s vs. novel microscopy method (κ = 0.68; good agreement), and Nugent’s vs. novel microscopy method without intermediary results (κ = 0.83; very good agreement). We also demonstrated that compared to Nugent’s method, as the golden standard, the novel microscopy method had high sensitivity and specificity (ranging from 75%–99.3%) and positive and negative predictive values (ranging from 88.8%–99.5%). Our method is based on a relative number of bacterial morphotypes, either rod forms (˃ 1.5 μm, lactobacilli) or non-rod forms (< 1.5 μm, bacterial vaginosis associated bacteria) under 200× magnification, which extends the surface of examined preparation, but without prolongation of observer’s working time. Conclusion. The novel microscopy method in diagnosing BV corresponded well with Nugent’s scoring system which allows it to be an alternative method in diagnosing BV. Furthermore, the novel microscopy method is based on a relative number of bacterial morphotypes that appeared to be flexible and can be reorganized in the way to categorize findings into only two groups: normal and BV, which makes it comparable to dichotomous Amsel’s clinical criterion.